Modeling and simulation of an electrolyser for the production of HHO in Matlab- Simulink (2019)
The electrolyzers work through an electrochemical process, their derivatives (H2, O2, and HHO) are used as enriching fuels due to the electrolysis of water, being cleaner than gasoline and diesel. This article presents the dynamic model of an alkaline electrolyzer that uses an electrolyte (KOH o NaHCO3) dissolved in distilled water to accelerate the production of oxyhydrogen (HHO). The model shows the phase change that occurs inside the electrolytic cell. The EES® software was used to determine the values of enthalpy, entropy, and free energy that vary during the electrochemical reaction; the equations were simulated in Matlab-Simulink® to observe their dynamic behavior. The Simulations presented varying every 5 g the electrolyte until reaching 20 g. The flow rate of HHO with potassium hydroxide (20 g) is higher than 0.02 L / s, and with sodium bicarbonate (20 g) it is above 0.0006 L / s, confirming what the literature of alkaline cells state, that the most efficient electrolyte for its energy conversion is KOH